"Something's Stalking Through the City of Smoke": Tracing the Ins and Outs of Gravity's Rainbow's London - Heikki Raudaskoski (Pynchon Notes, 1998)
I have a site in mind. It is an adulterous or, better, pre-adulterous bed. Here is a cite from the site.